POLA KOMUNIKASI KELUARGA DALAM MENANAMKAN TATA CARA BERPAKAIAN MELAYU DI KELURAHAN PERANAP KABUPATEN INDRAGIRI HULU - Rella Ningsih; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Way of dressed of men and women isno longer paying attention to ethics in the dressing.On men more delighted by imitate the outside culture, such as wearing torn long pants, wear boxer (shortpants) when gatheredortravelling, and leotardsclothes that show the posture of men body. While in the women should dress closes the nakedness, but most women have forgotten by the norm in dress, which they wear clothes that show their body or transparent dress. The flurry of parents in employment, as well as parents do not teach children to use Malay clothing in accordance with the values of Malay culture, making the child, adolescent or adult use clothing in accordance with the tastes and cultural influences from the outside. This research aims to know the pattern of family communication in instilling way of malay dress in Peranap Villageand factors that affect family communication patternin instilling way of malay dress in Peranap Village.This research used descriptive analysis with qualitative research and retrieval using a purposive sampling.Number of informantwas four with data collection techniques namely observation, interview and documentation. As for the legitimate examination of technique of data, researchers using the technique of prolongation of participation. The data obtained was processed to the reduction, served up to togenerated a general conclusion.The result of this research shows that there are existence of authoritarian communication patternin the pattern of family communication in instilling way of malay dressed in Peranap Village.There is a sense the attitude of resolute, angry, reproving violates, of punishment. Furthermore there is a pattern of communication democracy that freedom, openness and the rules agreed by members of the family. Factors that affect family communication patterns in instilling way of malay dress in Peranap Village namely self-esteem factor that reflects the personal self, authority and does not give rise to defamation or waffle in society. And inability to reveal where not being a statute or an obligation and there are other informants said incompetence revealed in Malay dress became a source of the problem.Keywords: Pattern, Communication, Family, Malay, Culture